Vibrations of Rotating Machinery Volume 2. Advanced Rotordynamics: Applications of Analysis, Troubleshooting and Diagnosis - Matsushita, Osami; Tanaka, Masato; Kobayashi, Masao; Keogh, Patrick; Kanki, Hiroshi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2019)
Building on the previous volume "Vibrations of Rotating Machinery - Volume 1. Basic Rotordynamics: Introduction to Practical Vibration Analysis," this book is intended for all practical designers and maintenance experts who are responsible for the reliable manufacturing and operation of rotating machinery. It opens with the dynamics of oil film bearings and their influences on unbalance, vibration resonance and the stability of rotor whirl motion. Subsequently, the book introduces readers to vibration diagnosis techniques for traditional ball bearings and active vibration control from magnetic bearings. Case studies on vibration problems and troubleshooting in industrial turbo machines are then presented and explained, showing rotor designers how to eliminate instability and modify resonance characteristics. Torsional vibration and other coupled vibration phenomena are discussed, and vibration measurement techniques and related signal processing procedures for vibration diagnosisare provided. Our latest three topics are included, covering: (a) the importance of the modeling order reduction (MOR) technique; (b) the approximate evaluation for oil-wheel/whip instability; and (c) a systematic method for shafting-blading coupled vibration analyses. In closing, a 100-question trial test is supplied as an example of the certification of vibration experts based on the ISO standard.
Basics of plain bearings -- Unbalance vibration of a rotor in plain bearings -- Stability of a rotor in plain bearings -- Vibration due to rolling bearings -- Vibration in active magnetic bearing rotor systems -- Case studies of forced vibration problems -- Case studies of self-excited vibration problems -- Torsional vibration and related coupled vibration -- Signal processing for rotor vibration diagnosis -- Trial examination for vibration expert certification -- Rotor vibration analysis program: MyROT.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Mechanical engineering; Software engineering; Multibody Systems and Mechanical Vibrations; Mechanical Engineering; Software Engineering